RAKYAT DALAM GOOD CORPORATE GOVERNANCE: POSISI, HUBUNGAN, DAN SKEMA KEADABAN - Imam Samroni (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
The relationship between state executor, business actor, and people or social order that enter Good Corporate Governance and Corporate Social Responsibility on an agenda is not necessarily in an mutual acord. The paper offers three schemes in strengthening the position and relationship of the people or social order among other stakeholders. Firstly, the attitude toward neoliberalism, which is the scheme to prepare the people or the social order using future research in managing the future. Secondly, the scheme of democracy choice that has been a must in the reason economic-politic conditions. And thirdly, the attitude toward “memetic engineering,” wich is the scheme to develop populist values parallel with nation plurality that they are accepted and are not constanly put in a contradiction.